Three new species of Artotrogidae (Copepoda, Siphonostomatoida) from the southeastern coast of Pernambuco State, Brazil - Neves, Elizabeth; Johnsson, Rodrigo (Zootaxa, 2008)
Three new copepod species, Bradypontius ancistronus sp. nov., Cryptopontius aesthetascus sp. nov. and Cryptopontius expletus sp. nov., of the siphonostomatoid family Artotrogidae are described based on specimens from sponge and algal hosts collected along the Brazilian coast. These findings represent the first records of artotrogid copepods from Brazil. Male Bradypontius ancistronus sp. nov. was found in association with sponges, and is characterized by having an unarmed P4 endopod that bears a distal hook-like projection on the third segment. Male Cryptopontius aesthetascus sp. nov., also recorded from sponges, differs from its congeners by a combination of characters that include a 12-segmented antennule, 2 setae on the inner lobe of the maxillule, 7 elements on the third exopodal segment of P1 and 9 elements on the third exopodal segment of P4. Female Cryptopontius expletus sp. nov. was recorded on algae, and can be distinguished from its congeners by having an 8-segmented antennule, 6 elements on the third endopodal segment of P1, 9 elements on the third exopodal segment of P4 and 3 setae on P5 exopod.